Pelayanan Publik Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Karimun ( Studi Kasus Pada Pelayanan Akta Kelahiran) - Aspalinda, Mety; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Birth certificate constitutes a tangible deed form as a sheet of paper that published by on duty demography and meaty Civil Registry information hits child id that is borne which is name, date of comes into the world, oldster name, and official signature in charge. Birth certificate thus, one any one gets to point out law relationship with oldster second. In this case on duty demography, and Karimun's Regency Civil Registry shall service society in each civil registry one of it birth certificate service. Registry civiling to constitute one of part of comprehensive registry system one State. Civil registry system at deep one State has main aim to result requested law document by prevailing State at that State. Of watch result at observational location apparently procedures it enough is hard divide oldster that wants to manage its child birth certificate, where is birth certificate management that necessarily enough cheap it was looked on precious to play favorites society because of marks sense agency that asks for more rate which more specified and of time facet be looked on so long in its management. This research intent to know public service in particular birth certificate service on on duty demography and Karimun's Regency Civil Registry. This research gets deskriftif kualitatif's character where downloading did by snowball's tech sampling. Result observationaling to point out service that gave by on duty demography and civil registry was walking with every consideration. It proved by medium condition and prasarana that don't be equal to,clerck ability that haven't created good and fast service and satisfying and office location distance that far.Key word: birth certificate, public service